Genomewide studies of histone deacetylase function in yeast - Bernstein, Bradley E. (The National Academy of Sciences, 2000)
The trichostatin A (TSA)-sensitive histone deacetylase (HDAC) Rpd3p exists in a complex with Sin3p and Sap30p in yeast that is recruited to target promoters by transcription factors including Ume6p. Sir2p is a TSA-resistant HDAC that mediates yeast silencing. The transcription profile of rpd3 is similar to the profiles of sin3, sap30, ume6, and TSA-treated wild-type yeast. A Ume6p-binding site was identified in the promoters of genes up-regulated in the sin3 strain. Two genes appear to participate in feedback loops that modulate HDAC activity: ZRT1 encodes a zinc transporter and is repressed by RPD3 (Rpd3p is zinc-dependent); BNA1 encodes a nicotinamide adenine dinucleotide (NAD)-biosynthesis enzyme and is repressed by SIR2 (Sir2p is NAD-dependent). Although HDACs are transcriptional repressors, deletion of RPD3 down-regulates certain genes. Many of these are down-regulated rapidly by TSA, indicating that Rpd3p may also activate transcription. Deletion of RPD3 previously has been shown to repress (“silence”) reporter genes inserted near telomeres. The profiles demonstrate that 40% of endogenous genes located within 20 kb of telomeres are down-regulated by RPD3 deletion. Rpd3p appears to activate telomeric genes sensitive to histone depletion indirectly by repressing transcription of histone genes. Rpd3p also appears to activate telomeric genes repressed by the silent information regulator (SIR) proteins directly, possibly by deacetylating lysine 12 of histone H4. Finally, bioinformatic analyses indicate that the yeast HDACs RPD3, SIR2, and HDA1 play distinct roles in regulating genes involved in cell cycle progression, amino acid biosynthesis, and carbohydrate transport and utilization, respectively.